1983
DOI: 10.1007/bf00123721
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis, enzymatic heterozygosity and inbreeding depression in natural populations of Drosophila melanogaster

Abstract: Brother-sister mating effects on offspring viability in natural populations of Drosophila melanogaster were analysed in relation to developmental homeostasis and enzymatic heterozygosity of the individuals constituting the sib pairs. High developmental homeostasis and high degree of heterozygosity are associated with a low inbreeding depression in offspring and, therefore, with a low frequency of major deleterious factors. These resuits are discussed in relation to maintenance of polymorphism in natural popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 86 publications
0
23
1
Order By: Relevance
“…In this context, departures from ideal conditions during ontogeny (i.e., environmental or genetic stress) may reduce the "effi.ciency" of normal developmental processes and increase the levei of FA (Palmer and Strobeck 1 1986;Parsons, 1990;Clarke, 1993;Mf!Jller and Swaddle, 1997) andlor DA (Mclntyre and Mossey, 2002;Hennessy et al, 2004;Schaefer et al 1 2006;DeLeon 1 2007;Ercan et al 1 2008;Klingenberg et al, 2010b;Barrett et al, 2012;Claes et al, 2012). Associations between heterozygosity and FA have been reported in mammals and other species (Soulé, 1979;Biémont, 1983;Leary et al, 1984;Palmer and Strobeck, 1986;Mitton, 1993;Vf!Jllestad, 1999;Leamy et al, 2001), with some exceptions (Wooten and Smith, 1986;Patterson and Paton, 1990;Beacham, American Journal of Physical Anthropology 1991; Britten 1 1996; Gilligan et ai., 2000;Leamy et al, 2001). Moreover, FA seems to increase with increasing homozygosityt hybridization, inbreedingt mutation Strobeck, 1986, 1992;Clarke, 1992;Mf!Jller and Swaddle, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, departures from ideal conditions during ontogeny (i.e., environmental or genetic stress) may reduce the "effi.ciency" of normal developmental processes and increase the levei of FA (Palmer and Strobeck 1 1986;Parsons, 1990;Clarke, 1993;Mf!Jller and Swaddle, 1997) andlor DA (Mclntyre and Mossey, 2002;Hennessy et al, 2004;Schaefer et al 1 2006;DeLeon 1 2007;Ercan et al 1 2008;Klingenberg et al, 2010b;Barrett et al, 2012;Claes et al, 2012). Associations between heterozygosity and FA have been reported in mammals and other species (Soulé, 1979;Biémont, 1983;Leary et al, 1984;Palmer and Strobeck, 1986;Mitton, 1993;Vf!Jllestad, 1999;Leamy et al, 2001), with some exceptions (Wooten and Smith, 1986;Patterson and Paton, 1990;Beacham, American Journal of Physical Anthropology 1991; Britten 1 1996; Gilligan et ai., 2000;Leamy et al, 2001). Moreover, FA seems to increase with increasing homozygosityt hybridization, inbreedingt mutation Strobeck, 1986, 1992;Clarke, 1992;Mf!Jller and Swaddle, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For instance some authors found a negative correlation between heterozygosity and FA (Soulé, 1979;Vrijenhoek and Lerman, 1982;Biémont, 1983;Leary et ai., 1984;Livshits and Kobyliansky, 1985;Mitton, 1993), but this vision is challenged by other studies that report absent or weak correlations (Beacham, 1991;Clarke and Oldroyd, 1996;V0llestad and Hindar, 1997). A meta-analysis conducted by V0llestad and Hindar (1997), on 118 individual samples of ectothermic and endothermic animais, concluded that heterozygosis and FA relationship is only weakly supported by available data, and that heterozygosis explains a very small amount of the variation in developmental instability among individuais and populations.…”
Section: American Joumal Of Physical Anthropologymentioning
confidence: 98%
“…Studies on symmetry were carried out on morphological characters with bilateral distribution (S OULE , 1979 ;L EARY et al, 1983 ;B IEMONT , 1983) The comparisons made between HET and PHP individuals were similar in type to those carried out in other works dealing with individuals taken from natural populations. In both cases the individuals were classified according to their level of homozygosity for some biochemical loci.…”
Section: Introductionmentioning
confidence: 77%
“…E ANES (1978) came to a similar conclusion after examining 6 polymorphic loci and 2 morphological traits in the monarch butterfly, Danaus plexippus. Enzyme heterozygosity has been reported as associated with either growth rate or developmental stability in a wide range of organisms : birds (F LEISCHER et al , 1983) (G UNAWAN , 1981 ;B IEMONT , 1983). However, there are a few results where these correlations were not found (H ANDFORD , 1980 ;McANDREW et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found evidence for such a relationship in fish and other organisms (Vrijenhoek and Lerman 1982;Biemont 1983;Lear-y et al 1984b). To examine the relationship between these two variables in Snake River spring/summer chinook salmon, we computed correlation coefficients between individual heterozygosity (H = the proportion of loci heterozygous in an individual) and three different measures of asymmetry: the absolute value of asymmetry (1 ~jI >; the index of fluctuating Table 18.…”
Section: Asymmetry and Heterozygositymentioning
confidence: 98%